Aspek biologi kepiting bakau (Scylla sp.) di Perairan Teluk Bintuni, Papua Barat - Pranata, Bayu; Kusuma, Aradea Bujana; Lapadi, Ida; Sala, Ridwan; Ayamiseba, Yunita; Wyrasti, Andi Fajeriani (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: The waters of Bintuni Bay have potential mangrove crab (Scylla sp.) resources. Mud crabs are aquatic biota that have high economic value. Information about the biological aspects of mangrove crabs in the waters of Bintuni Bay is still very minimal. This research aims to examine the size structure, growth patterns, condition factors and gon-ad maturity level (TKG) of mud crabs in the waters of Bintuni Bay. The research was carried out from May to July 2023. The research results showed that the average carapace width and weight of male mud crabs were 13.6 cm and 553.2 grams. Meanwhile, the average size of the shell width and weight of female mud crabs is 12.5 cm and 284.1 grams. The average size of mangrove crabs caught is included in the catchable category (KKP Ministerial Regulation No. 16 of 2022). The growth pattern of male mud crabs is isometric (b = 3.15), while the growth pattern of female mud crabs is negative allometric (b = 2.12). The condition factor values for male and female mud crabs are 1.01 and 1.03. The results of TKG observations showed that 78.4% of female crabs were in TKG I and II, meaning that 50% of the shrimp caught had not yet reached TGK III and IV at the time of the research.